Genetic analysis of CHCHD2 gene in Chinese Parkinson's disease. Issue 8 (14th September 2016) - Li, Nan‐Nan; Wang, Ling; Tan, Eng‐King; Cheng, Lan; Sun, Xiao‐Yi; Lu, Zhong‐Jiao; Li, Jun‐Ying; Zhang, Jin‐Hong; Peng, Rong
Abstract : Recently, mutations in the coiled‐coil‐helix–coiled‐coil‐helix domain containing 2 ( CHCHD2 ) gene have been identified in Japanese families with autosomal dominant Parkinson's disease (PD) and two single nucleotide variants (rs10043 and Pro2Leu) increased risk of sporadic PD. The role of CHCHD2 in PD susceptibility in other Asian populations still remains to be clarified. In a large Chinese cohort from mainland China (31 familial PD patients, 1, 027 sporadic PD patients, and 1, 095 health controls), we examined the association of rs10043 and Pro2Leu variants in CHCHD2 with PD. All subjects were homozygous for rs10043. Moreover, we detected six patients (0.57%, one of the six patients has family history) and three controls (0.27%) with a heterozygous Pro2Leu variant. Though the frequency of Pro2Leu variant was two times higher in PD compared to controls, the difference did not reach significance in genotypic distribution ( P  = 0.47) or allelic distribution ( P  = 0.47). However, our meta‐analysis in Asian populations revealed that the frequency of Pro2Leu variant was significantly higher in PD patients than in controls ( P  = 0.0002). Our study suggests that Pro2Leu in CHCHD2 may be a risk factor for PD among Asians. © 2016 Wiley Periodicals, Inc.